The Effect of Contextual Interference on Spatial Accuracy and Motor Reprogramming of Sequential Motor Task in People with Parkinson's Disease - Parvin Mohammadi Farsani; Hamidreza Taheri Torbati; Mehdi Sohrabi; Ali Shoeibi (رشد و یادگیری حرکتی ورزشی, 2024)
Introduction: The goal of research is to create a learning environment that can increase learning. This study aimed to investigate the effect of contextual interference on spatial accuracy and motor reprogramming of the sequential motor task in people with Parkinson's disease.Methods: The research method is a quasi-experimental type with a pre-test and post-test research design. 64 people with Parkinson's disease (mean age = 62.93 ± 3) were selected by convenience sampling method and randomly assigned into four equal groups (16 people) including blocked - high similarity, blocked - low similarity, random - high similarity, and random - low similarity. The participants performed 180 trials (12 blocks of 15 trials) for three sequential movement tasks. The error of movement patterns performance was calculated in all stages. In the acquisition stage, the 2 (contextual interference) × 2 (sequence similarity) × 11 (acquisition blocks) ANOVA with repeated measures of the last factor, and for the retention stage, the 2 (contextual interference) × 2 (similarity of sequence) × 3 (stages) ANOVA with repeated measures of last factor, and for the transfer and reprogramming stages, the 2 (contextual interference) × 2 (sequence similarity) ANOVA were used at P=0.05 level of significance.Results: The results showed that in the acquisition phase, the blocked-high similarity group performed better, and the interactive effect of the group and sequence similarity was not significant in the retention and transfer stages. In the reprogramming phase, the random-high similarity group was better.Conclusion: According to the elaboration hypothesis, random practice increases the strength of memory representation and forms deeper processing in memory.